R. MONEO - La vida de los edificios - Díez Medina, Carmen (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2019)
Rafael Moneo La vida de los edificios Barcelona: Acantilado, 2017, 220 pages. Language: Spanish. Softcover. 16 €. ISBN-10: 8416748616; ISBN-13: 978-8416748617